ANALISIS PENGELOLAAN PIUTANG PADA PT.WIRATIMUR SEGARA DI SAMARINDA - -, Kartika Aprilia (EKONOMIA, 2014)
This study was conducted to determine whether the management of accounts receivable that have been implemented in accordance with the internal control, the data used is primary data obtained from questionnaires to identify elements - elements of internal control. Questionnaires were used to be covered with a choice of "Yes" and "No" to leaders and employees at PT. Wiratimur Segara. The calculation is done by comparison of the relative value formula. Based on the research results, it is known that the management of accounts receivable that have been carried out by PT. Wiratimur Segara Samarinda has been going well. Evidenced by the results of the analysis of the Internal Control Questionnaries (ICQ) that scored 84% were categorized as relatively "good". This situation reflects the management of receivables has been going well in accordance with the internal control. But there are internal control procedures in the collection of accounts receivable that have not adequately implemented, the billing is not done on a regular basis to customers whose claim has matured.